Duolingo Application: Enriching Vocabulary Mastery Of EFL Students - Selviana H, Selviana H; Anggreni, Afrillia; Jamiluddin, Jamiluddin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research exposes vocabulary mastery of eleventh-grade students by utilizing Duolingo apps. Critical issues namely limited vocabulary knowledge, low motivation, and lack of practice had hindered students' language development. By employing a cluster random sampling method, the research involved a pretest and posttest to evaluate students' vocabulary before and after using the Duolingo application. Various vocabulary assessments in terms of making sentences, multiple-choice, and matching exercises were distributed to ensure a comprehensive evaluation of students' understanding in concrete nouns, action verbs, and descriptive adjectives. The results indicate that there is a statistically increase of the students’ score in the experimental group from pretest to posttest (71.68 to 73.92). The results of the paired t-test also present a statistically significant difference (t = -5.209, p = 0.000). In contrast, the control group using conventional techniques only showed a small increase from 71.68 to 73.92, and the results of the t-test showed no significant difference (t = -1.430, p = 0.166). This suggests that the Duolingo application effectively enhances students' vocabulary mastery and overall language proficiency. It can be concluded that integrating innovative teaching methods, such as gamified learning through Duolingo, can significantly boost students' motivation and engagement in language learning. Therefore, teachers can explore diverse teaching strategies that cater to various learning styles and encourage students to actively participate in language practice through interactive features of the application. Overall, this research contributes valuable insights into the role of technology in language learning and its potential to transform traditional learning approaches.